2021
DOI: 10.1016/j.xkme.2021.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Group-Based Exercise in CKD Stage 3b to 4: A Randomized Clinical Trial

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(29 citation statements)
references
References 60 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Anand et al [ 31 ] conducted a comparative study to evaluate the impact of mHealth combined twice weekly directed exercise session versus only exercise sessions on daily step counts in 56 patients with CKD stage 3b-4. The intervention lasted eight weeks, followed by an 8-week passive follow-up period.…”
Section: Resultsmentioning
confidence: 99%
“…Anand et al [ 31 ] conducted a comparative study to evaluate the impact of mHealth combined twice weekly directed exercise session versus only exercise sessions on daily step counts in 56 patients with CKD stage 3b-4. The intervention lasted eight weeks, followed by an 8-week passive follow-up period.…”
Section: Resultsmentioning
confidence: 99%
“…Following duplicate removal, the title and abstract of 3,934 articles were screened and the full texts of 105 articles were assessed for eligibility. Finally, eight studies (four RCT’s [ 36 39 ]) and four single arm [ 40 43 ]) with baseline sample sizes ranging from n = 17 [ 38 ] to n = 340 participants [ 39 ], resulting in 550 participants were included in the review (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The stages of CKD ranged from 1 through to haemodialysis and kidney transplant recipients (Table 1 ). Reported primary outcomes included self-management of CKD reported via self-report questionnaires [ 37 , 41 ] physical and psychological outcomes [ 36 , 39 ] and feasibility and acceptability [ 38 , 40 , 42 , 43 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given the association between increased physical activity levels and mortality in the CKD population [ 81 ], there were only five studies which examined this outcome [ 41 , 62 , 66 , 68 , 73 ]. The previous review from 2019 did not include any studies reporting physical activity as an outcome [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…An RCT [73] investigated the effect of a wearable on physical activity levels, they reported that the intervention was feasible, although steps per day decreased in the intervention group, the minutes of moderate to vigorous physical activity increased. There appeared to be no effect on HRQoL and mental health measures during the study [73]. A similar study [75] found a wearable activity tracker was feasible and acceptable in encouraging physical activity in older transplant recipients.…”
Section: Other Ehealth Interventionsmentioning
confidence: 99%